2016
DOI: 10.1042/bst20150200
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyltransferase engineering for carbohydrate synthesis

Abstract: Glycosyltransferases are powerful tools for the synthesis of complex and biologically important carbohydrates. Wild-type glycosyltransferases may not have all the properties and functions that are desired for large-scale production of carbohydrates that exist in nature and those with non-natural modifications. With the increasing availability of crystal structures of glycosyltransferases, especially those in the presence of donor and acceptor analogs, crystal structure-guided rational design has been quite suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 100 publications
(124 reference statements)
0
46
0
Order By: Relevance
“…34 Previous studies have demonstrated that glycosyltransferases are amenable to enzyme-substrate engineering, wherein the active site is modified to accept a non-native substrate. 35 Of particular relevance, the enzymes -1,4-galactosyltransferase 1 (4Gal-T1) and O-linked -Nacetylglucosamine transferase (O-GlcNAc transferase) have been rationally designed to accommodate nucleotide sugars bearing chemical handles. [36][37][38] Both of these engineered glycosyltransferases demonstrate expanded substrate specificity, as they still use their native substrates, UDP-galactose and UDP-GlcNAc, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…34 Previous studies have demonstrated that glycosyltransferases are amenable to enzyme-substrate engineering, wherein the active site is modified to accept a non-native substrate. 35 Of particular relevance, the enzymes -1,4-galactosyltransferase 1 (4Gal-T1) and O-linked -Nacetylglucosamine transferase (O-GlcNAc transferase) have been rationally designed to accommodate nucleotide sugars bearing chemical handles. [36][37][38] Both of these engineered glycosyltransferases demonstrate expanded substrate specificity, as they still use their native substrates, UDP-galactose and UDP-GlcNAc, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The technique of directed evolution (DE) may be more useful in such cases. To restrict the need to screen a large mutational library, variation of this semi-rational method can be employed [ 148 ]. For example, iterative site-saturation mutagenesis (ISM), where a critical amino acid is replaced by all other 19 amino acids at that position, can be used to select for the most efficient GT which can be further improved in the second round, by targeting another residue in the active-site.…”
Section: Plant Glycosyltransferases: Versatile Players In Biotechnmentioning
confidence: 99%
“…However, glycosyltransferases can be promiscuous in acceptor and donor substrates, thereby providing a rich source of biocatalysts with potentially exploitable side reactions. For example, human blood group galactosyltransferase and bovine β4GalT1 have been reported to display activity with multiple UDP-donor substrates including UDP-Glc [42][43][44] , while Neisseria meningitidis LgtB displays activity towards multiple acceptor substrates 45 . The rates of activity on alternative acceptors and donors have in many cases been demonstrated to be sufficient for exploitation of the promiscuous activity in synthesis of glycosides 42,[44][45][46][47][48] .…”
Section: Introductionmentioning
confidence: 99%